102k views
3 votes
How do you use the additive inverse to evaluate an expression that uses subtraction?

2 Answers

4 votes

Answer:

Additive inverse is the negative of the number, i.e. what you add to the number to get zero.

So the additive inverse of number b is - b

Additive inverse of 4 is - 4.

Then, you can verify the subtraction is the same that add the additive inverse.

For example subtracting 4 from 10 (10 - 4) is the same that adding -4:

10 - 4 = 10 + (-4).

Then given any expression if you have to subtract other expressión you just add the addive inverse of the second expression.

For example: given A(x) = x^2 + 3x + 5 and B(x) = 2x + 4

Find A(x) - B(x) = A(x) + [-B(x)]

=> x^2 + 3x + 5 + (-2x -4) = x^2 + 3x - 2x + 5 - 4 = x^2 + x + 1

Explanation:

hope this helped :)

User MeTitus
by
6.4k points
3 votes
The additive inverse of a number is what you add to a number to create the sum of zero. So in other words, the additive inverse of x is another number, y, as long as the sum of x + y equals zero. The additive inverse of x is equal and opposite in sign to it (so, y = -x or vice versa). For example, the additive inverse of the positive number 5 is -5. That's because their sum, or 5 + (-5) = 0.
User Mosceo
by
7.6k points